Heave Behavior of Granular Pile Anchor-Foundation System (GPA-Foundation System) in Expansive Soil (Journal of Engineering, 2014)
Granular  Pile  Anchor  (GPA)  is  one  of  the  innovative  foundation  techniques,  devised  for mitigating heave of footing resulting from the expansive soils. This research attempts to study the heave behavior of (GPA-Foundation System) in expansive soil. Laboratory tests have been conducted on an experimental model in addition to a series of numerical modeling and analysis using the finite element package PLAXIS software. The effects of different parameters, such as (GPA) length (L) and diameter (D), footing diameter (B), expansive clay layer thickness (H) and presence of non-expansive clay are studied. The results proved the efficiency of (GPA) in reducing the heave of expansive soil and showed that the heave can be reduced with increasing length and diameter of (GPA). The heave of (GPA-Foundation System) is controlled by three independent variables these are (L/D) ratio, (L/H) ratio and (B/D) ratio. The heave can be reduced by up to (38 %) when (GPA) is embedded in expansive soil layer at (L/H=1) and reduced by about (90 %) when (GPA) is embedded in expansive soil and extended to non- expansive clay (stable zone) at (L/H=2) at the same diameter of (GPA) and footing. An equation (mathematical mode1) was obtained by using the computer package (SPSS 17.0) for statistical analysis based on the results of finite element analysis relating the maximum heave of (GPA-Foundation System) as a function of the above mentioned three independent variables with coefficient of regression of (R2 = 92.3 %).